THE ROLE OF TRAINING, MOTIVATION AND ORGANIZATIONAL CULTURE ON WORK TEACHER’S PERFORMANCE AT MIN 4 LAMPUNG TIMUR - Eka Rahmawati; Syaiful Bakhri (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The role of the teacher as an educator has a very important influence in improving the quality of learning in madrasas. The ability of human resources must be truly tested so that they are able to do all the work correctly and produce perfect performance, both in quantity and quality. The purpose of this study was to determine the effect of training, motivation, and organizational culture on teacher performance at MIN 4 East Lampung. This research uses quantitative methods. Data collection was carried out using questionnaires, observations and interviews. The population and sample in this study were all 30 teachers at MIN 4 East Lampung. The analytical tool used is multiple linear regression using SPSS 25. From the multiple linear regression analysis, the result is Y = 4.114+0.174 X1+0.218 X2+0.527 X3. The results of the Pearson product moment coefficient test were 0.367 and the coefficient of determination or R-Square was 0.987 which means that the independent variables (Training, Motivation, Organizational Culture) have a significant effect of 98.7% on the dependent variable (Teacher Performance). The results of this study indicate that both partially and simultaneously training, motivation and organizational culture have an influence on teacher performance. Keywords: training, motivation, organizational culture, teacher performance